Mechanical Assessment of Glass Ionomer Cements Incorporated with Multi-Walled Carbon Nanotubes for Dental Applications - Manuela Spinola; Amanda Maria Oliveira Dal Piva; Patrícia Uchôas Barbosa; Carlos Rocha Gomes Torres; Eduardo Bresciani (MDPI AG, 2021)
Background: Nanoparticles such as multi-walled carbon nanotubes present resistance, resilience and biocompatibility with human tissues and could be incorporated into glass ionomer cement materials to improve their characteristics. Therefore, the aim of the present study was to evaluate the effect of multi-walled carbon nanotube (MWCNT) incorporation on different glass ionomer cements' compressive (σc) and diametral tensile strengths (σt). Methods: Eighty (80) specimens were divided into four groups (N = 20/gr) according to the glass ionomer cement type (conventional and high-viscosity) and the presence or absence of multi-walled carbon nanotubes. Samples were kept in water for 24 h prior to the tests. Data were analyzed using two-way ANOVA and Tukey's test (p = 0.05). Results: For both σc (p = 0.1739) and σt (p = 0.2183), the glass ionomer cements' viscosity did not influence the results. The presence of MWCNTs decreased the mean compressive strength values (p = 0.0001) and increased the diametral tensile strength (p = 0.0059). For both conventional and high-viscosity glass ionomer cements, the compressive strength values were higher than the tensile strength data. Conclusions: Regardless of the cement viscosity, the multi-walled carbon nanotube incorporation reduced the compressive strength and increased the tensile strength values.